2019
DOI: 10.1249/jes.0000000000000179
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ribosome Biogenesis During Skeletal Muscle Hypertrophy

Abstract: An increase in ribosomal capacity is a hallmark of the hypertrophying muscle. We review evidence demonstrating that transcription of ribosomal RNA genes is necessary for the increase in ribosomal capacity, and this is critical for muscle growth in human and animal models of hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…Ribosomes are the molecular factories responsible for protein synthesis, which is a key process in the long-term adaptive response to exercise in skeletal muscle (Figueiredo, 2019a;. Ribosome biogenesis is stimulated by muscle loading (Figueiredo & McCarthy, 2019b; Kim et al, 2019;von Walden, 2019b), and the magnitude of de novo synthesis of ribosomes is proportional to the amount of load-induced adult muscle hypertrophy in both rodents (Nakada et al, 2016) and humans (Figueiredo et al, 2015;Stec et al, 2016;Hammarstrom et al, 2020). Mechanical loading rapidly induces RNA Polymerase I (Pol I) transcription of ribosomal DNA (rDNA), as assessed by 45S pre-rRNA transcription levels and accumulation of rRNA (von Walden et al, 2012b;Kirby et al, 2016;Figueiredo et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomes are the molecular factories responsible for protein synthesis, which is a key process in the long-term adaptive response to exercise in skeletal muscle (Figueiredo, 2019a;. Ribosome biogenesis is stimulated by muscle loading (Figueiredo & McCarthy, 2019b; Kim et al, 2019;von Walden, 2019b), and the magnitude of de novo synthesis of ribosomes is proportional to the amount of load-induced adult muscle hypertrophy in both rodents (Nakada et al, 2016) and humans (Figueiredo et al, 2015;Stec et al, 2016;Hammarstrom et al, 2020). Mechanical loading rapidly induces RNA Polymerase I (Pol I) transcription of ribosomal DNA (rDNA), as assessed by 45S pre-rRNA transcription levels and accumulation of rRNA (von Walden et al, 2012b;Kirby et al, 2016;Figueiredo et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that despite the increased rRNA after an acute RE, we could not detect a concomitant change in total RNA expression. Although the mechanism of discrepancy between the change in rRNA content and total RNA content is unclear, one possible explanation is that an difficulty to precisely measure small change in the rRNA, since the total RNA contains other RNAs such as small RNA, tRNA, and mRNA (Figueiredo and McCarthy, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study observed that resting intracellular ribosomal content is highly correlated to the MPS (Millward et al, 1973). Moreover, recent evidence suggests that the capacity of ribosome biogenesis is relevant to the response of load-induced skeletal muscle hypertrophy (von Walden et al, 2012;Kirby et al, 2015;Figueiredo and McCarthy, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Resistance and endurance training increase skeletal muscle ribosome biogenesis and mitochondrial biogenesis, respectively. Mitochondrial biogenesis increases aerobic capacity ( Costill et al, 1976 ; Burgomaster et al, 2008 ; Yeo et al, 2008 ; Murias et al, 2011 ; Cochran et al, 2014 ; Vigelso et al, 2014 ), and ribosome biogenesis has been associated with skeletal muscle hypertrophy [reviewed in ( Chaillou et al, 2014 ; Wen et al, 2016 ; Mcglory et al, 2017 ; Bamman et al, 2018 ; Roberts et al, 2018a ; Figueiredo and Mccarthy, 2019 ; Kim et al, 2019 )]. It is generally believed that skeletal muscle adaptations to exercise are highly specific.…”
Section: Introductionmentioning
confidence: 99%